2022
DOI: 10.1007/s12105-022-01454-5
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 Gene Amplification and Expression of MDM2 and CDK4 are Rare in Ossifying Fibroma of Craniofacial Bones

Abstract: Ossifying fibroma of the craniofacial bones is a fibro-osseous lesion characterized by varied patterns of bone formation in a fibroblastic stroma. Ossifying fibroma is a putatively benign lesion with no reports of malignant transformation or metastasis. Differentiation from other fibro-osseous lesions can be challenging necessitating synthesis of clinical, radiological and pathological findings. The molecular pathogenesis of ossifying fibroma is poorly understood but recent studies have reported MDM2 gene ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Focal MDM2 amplification was not identified in any case though case 7 showed gain of MDM2 secondary to tetrasomy of chromosome 12. The only case (case 6) that showed MDM2 amplification by FISH in our prior study [13] did not display MDM2 amplification by NGS in the current analysis. This discrepancy is difficult to explain.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Focal MDM2 amplification was not identified in any case though case 7 showed gain of MDM2 secondary to tetrasomy of chromosome 12. The only case (case 6) that showed MDM2 amplification by FISH in our prior study [13] did not display MDM2 amplification by NGS in the current analysis. This discrepancy is difficult to explain.…”
Section: Discussionmentioning
confidence: 46%
“…[7]. A separate study using FISH demonstrated MDM2 amplification in only 2% of OF without concordant protein overexpression [13]. Similar conflicting results were also reported in the copy number profiles of OF; whereas some studies showed large-scale CNAs, others showed none [12,16].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations